On Cesàro and Copson sequence spaces with weights - S. H. Saker; Maryam M. Abuelwafa; Ahmed M. Zidan; Dumitru Baleanu (Journal of Inequalities and Applications, 2021)
Abstract In this paper, we prove some properties of weighted Cesàro and Copson sequences spaces by establishing some factorization theorems. The results lead to two-sided norm discrete inequalities with best possible constants and also give conditions for the boundedness of the generalized discrete weighted Hardy and Copson operators.